Facilitators and barriers to in vitro diagnostics implementation in resource-limited settings: A scoping review - Monica Ansu-Mensah; Desmond Kuupiel; Emmanuel A. Asiamah; Themba G. Ginindza (AOSIS, 2023)
Background: The World Health Organization (WHO) developed the model list of essential in vitro diagnostics (EDL) to guide countries to develop and update point-of-care (POC) per their disease priorities. The EDL includes POC diagnostic tests for use in health facilities without laboratories; however, their implementation might face several challenges in low- and middle-income countries (LMICs). Aim: To identify facilitators and barriers to POC testing service implementations in the primary health care facilities in the LMICs. Setting: Low- and middle-income countries. Methods: This scoping review was guided by Arksey and O'Malley's methodological framework. A comprehensive keyword search for literature was conducted in Google Scholar, EBSCOhost, PubMed, Web of Science and ScienceDirect using the Boolean terms ('AND' and 'OR'), as well as Medical Subject Headings. The study considered published articles in the English language from 2016 to 2021 and was limited to qualitative, quantitative and mixed-method studies. Two reviewers independently screened the articles at the abstract and full-text screening phases guided by the eligibility criteria. Data were analysed qualitatively and quantitatively. Results: Of the 57 studies identified through literature searches, 16 met this study's eligibility criteria. Of the 16 studies, 7 reported on both facilitators and barriers; and the remainder reported on only barriers to POC test implementation such as inadequate funding, insufficient human resource, stigmatisation, et cetera. Conclusion: The study demonstrated a wide research gap in facilitators and barriers, especially in the general POC diagnostic test for use in health facilities without laboratories in the LMICs. Extensive research in POC testing service is recommended to improve service delivery. Contribution: This study's findings contribute to a few works of literature on existing evidence of POC testing.